Evaluating the effects of sodium metabisulfite on the cognitive and motor function in Drosophila melanogaster - Nas, John SB.; Medina, Paul MB. (Narra J, 2024)
Sodium metabisulfite is widely used as a preservative in many food and beverage products, yet its potential effects on cognitive and motor functions at low concentrations remain poorly understood. Evaluating learning, short-term memory, and motor activity is essential, as these functions are critical indicators of neurological health and could be impacted by low-level exposure to sodium metabisulfite. The aim of this study was to investigate the effects of sublethal concentrations of sodium metabisulfite on cognitive and motor functions using Drosophila melanogaster (fruit flies) as the model organism. Different levels of sodium metabisulfite were administered to male and female fruit flies, and their learning and short-term memory were observed. Additionally, their climbing activity with and without stressors (heat shock, ultraviolet A exposure, or energy deprivation) was examined. Our findings indicated that sodium metabisulfite did not impair learning, short-term memory, or motor activity. Furthermore, sodium metabisulfite did not affect the motor activity of fruit flies under heat, ultraviolet A, and energy-deprived conditions. In conclusion, our results suggested that the sublethal concentration of sodium metabisulfite did not harm cognitive and motor functions and did not exacerbate the effects of environmental stressors.